Barriers to Access to Palliative Care in Colombia: A Social Mapping Approach Involving Stakeholder Participation - Lina María Vargas-Escobar PhD; Miguel Antonio Sánchez-Cárdenas PhD; Angie Carolina Guerrero-Benítez MSc; Vilma Katherine Suarez-Prieto MSc; Jenny Rocío Moreno-García MSc; Ángela María Cañón Piñeros MA; Luisa Fernanda Rodríguez-Campos MD; Marta Ximena León-Delgado MD (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2022)
This study aimed to identify barriers to access to palliative care through a social mapping approach. In Colombia, the barriers to access to palliative care denote an enormous geographic disparity of resources and health needs, making it necessary to conduct community-based participatory research using an approach such as social mapping. A qualitative research design was used. Stakeholders from health insurance companies, regulatory authorities, regional health secretariats, health care professionals, patient and caregiver organizations, scientific societies, and medical journalists from 7 Colombian regions participated. It involved 3 stages. Stage 1: Semi-structured, audio-recorded interviews were conducted with 36 stakeholders and were subsequently transcribed and analyzed. Stage 2: An electronic survey was conducted to obtain feedback on the first outline of the map and the categories that emerged from stage 1. Stage 3: The nominal group technique was used to analyze and validate the barriers to access to palliative care included in the final map. The COREQ checklist was used. Twenty-seven barriers to access to palliative care related to limited availability of medications, stakeholders’ poor knowledge of regulations, limited formal education in palliative care, few patients’ support networks, patient care fragmentation, few specialized programs of palliative care, and mistaken beliefs about palliative care were identified. Stakeholders’ diverse perspectives and opinions were crucial to understanding the development of palliative care in Colombia and its challenges. Better knowledge about palliative care can open opportunities to overcome the barriers identified in this study, directly impacting access to palliative care.